2018
DOI: 10.1016/j.trci.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the compound Chinese medicine SaiLuoTong in vascular dementia: A randomized clinical trial

Abstract: IntroductionNo licensed medications are available to treat vascular dementia (VaD).MethodsPatients were randomly assigned to experimental groups (SaiLuoTong [SLT] 360 or 240 mg for groups A and B for 52 weeks, respectively) or placebo group (SLT 360 mg and 240 mg for group C only from weeks 27 to 52, respectively).ResultsThree hundred twenty-five patients were included in final analysis. At week 26, the difference in VaD Assessment Scale–cognitive subscale scores was 2.67 (95% confidence interval, 1.54 to 3.81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 30 publications
4
50
1
Order By: Relevance
“…The SLT formula consists of standard extracts of specific dosages of Panax ginseng C. A. Meyer (ginseng), Gingko biloba L. (ginkgo), and Crocus sativus L. (saffron). The chemical profile and ratio of the three herbal extracts had been determined and studied in detail previously [ 10 , 11 ]. The cognitive enhancing effect of SLT has been demonstrated in both preclinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The SLT formula consists of standard extracts of specific dosages of Panax ginseng C. A. Meyer (ginseng), Gingko biloba L. (ginkgo), and Crocus sativus L. (saffron). The chemical profile and ratio of the three herbal extracts had been determined and studied in detail previously [ 10 , 11 ]. The cognitive enhancing effect of SLT has been demonstrated in both preclinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Through in vivo and in vitro studies, various components of herbal medicine have been found to possess the ability to intervene in aging-related diseases by activating telomerase, increasing antioxidant capacity, reducing apoptosis and anti-inflammatory activities, and regulating aging-related pathways and exosomes. We also summarized the clinical randomized controlled trials (RCTs) of herbal medicine in the treatment of aging-related diseases ( Table 3) [240][241][242][243][244][245][246][247][248][249][250]. These trials found that herbal medicine displays certain clinical efficacy in the treatment of agerelated diseases such as type 2 diabetes, vascular dementia, AD, and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…A few clinical studies on AMD exist, but this disorder is considered to be related to the special technique used for intravitreal administration when treating macular lesions. Of note, as shown in Table 3, there are some adverse reactions in the clinical use of herbal medicines, including gastrointestinal discomfort, dry mouth, and abnormal alanine aminotransferase [245][246][247]250]. Experimental studies had also found that there was a dose-response curve characterized by stimulation at a low dose and inhibition at a high dose.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemical or growth factor based anti-aging compounds may raise unexpected side effects 25 . On the other hand, the safety of herbal medicine used for designing of cosmetic products is highly acceptable 26,27 . In this study, high passage of HDFs exhibited delayed cell growth rate accompanied by increase of p53 and SA-β-gal.…”
Section: Discussionmentioning
confidence: 99%